2011
DOI: 10.3390/ijms12096255
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Phenolic Antioxidant Extraction from Wuweizi (Schisandra chinensis) Pulp Using Random-Centroid Optimazation Methodology

Abstract: The extraction optimization and composition analysis of polyphenols in the fresh pulp of Wuweizi (Schisandra chinensis) have been investigated in this study. The extraction process of polyphenols from Wuweizi pulp was optimized using Random-Centroid Optimization (RCO) methodology. Six factors including liquid and solid ratio, ethanol concentration, pH, temperature, heating time and extraction times, and three extraction targets of polyphenol content, antioxidant activity and extract yield were considered in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Bioactivities of bee pollen Bioactivities of bee pollen against DPPH radicals (Wu et al, 2011). Dandelion fl ower extracts containing fl avonoids and coumaric derivatives possessed marked antioxidant activities (Hu and Kitts, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Bioactivities of bee pollen Bioactivities of bee pollen against DPPH radicals (Wu et al, 2011). Dandelion fl ower extracts containing fl avonoids and coumaric derivatives possessed marked antioxidant activities (Hu and Kitts, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Wang (2013) reported that the content of TP in the fruits of A. arguta was 214.8 mg/100 g, whereas Zuo et al (2012) claimed that value to be higher. Wu et al (2011) noted that the content of total phenols in S. chinensis fruits was 184.7 mg/100 g, and the content of anthocyanins was 17.9 mg/100 g of fresh weight. The results obtained in the present study were similar to those provided by Wu et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (2011) noted that the content of total phenols in S. chinensis fruits was 184.7 mg/100 g, and the content of anthocyanins was 17.9 mg/100 g of fresh weight. The results obtained in the present study were similar to those provided by Wu et al (2011). Pliszka et al (2009), who performed extraction using citric acid, concluded that the content of total phenols in G. procumbens fruits ranged from 180.0 mg to 495.2 mg/100 g of fresh matter, and the content of anthocyanins varied from 7.83 mg to 13.11 mg/100 g of fresh matter, depending on the date of fruit harvest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present research, ethanol and water were adopted as the extraction media because of their environmentally friendly effects and non-toxicity for human health. Among various factors contributing to the efficiency of the solvent extraction process and the recovery of antioxidant compounds from natural materials, ethanol concentration, extraction time, extraction temperature, the number of extraction cycles, and the solid-to-solvent ratio are often investigated (Yang et al, 2009;Wu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%